2019
DOI: 10.1093/arclin/acz035.04
|View full text |Cite
|
Sign up to set email alerts
|

Automated scoring of the Rey-Osterrieth Complex Figure Test using a deep-learning algorithm

Abstract: Objective To validate a fully automated scoring algorithm for the Rey-Osterrieth Complex Figure Test (ROCFT) by comparing the scoring results of the algorithm to the results of human raters. Method The algorithm consisted of a cascade of deep neural networks which were trained on human rater scores to extract the 18 segments of the figure, and to quantify the patient’s performance. Algorithm results were compared to six exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…At the same time, combined with machine learning algorithms, it can build classification and diagnosis models of different diseases. A recent study used the deep learning algorithm to automate ROCF scoring, which has high performance and is close to the reliability of human raters ( 78 ). Future research should use machine learning technology to provide information about the neuropsychological structure of different neuropsychiatric diseases and gradually establish a new digital scoring method to standardize clinical practice, such as a digital ROCF feature selection analysis algorithm.…”
Section: Conclusion and Prospectmentioning
confidence: 99%
“…At the same time, combined with machine learning algorithms, it can build classification and diagnosis models of different diseases. A recent study used the deep learning algorithm to automate ROCF scoring, which has high performance and is close to the reliability of human raters ( 78 ). Future research should use machine learning technology to provide information about the neuropsychological structure of different neuropsychiatric diseases and gradually establish a new digital scoring method to standardize clinical practice, such as a digital ROCF feature selection analysis algorithm.…”
Section: Conclusion and Prospectmentioning
confidence: 99%
“…Poorer copying of a figure by a given patient in comparison with that by normal healthy controls could suggest Alzheimer's disease (AD). 7 It has been reported that RCF is one of neuropsychological tests with adequate sensitivity and specificity for discriminating patients with different neuropsychological conditions such as dementia, MCI, depression, and mild head injury. 8 Many clinicians have used RCF for diagnosing MCI and dementia to improve their clinical decisions.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Other studies have reported a fully automated scoring algorithm for RCF by comparing scoring results of the algorithm to results of manual scoring. 7 The algorithm consisting of a cascade machine learning model was trained on manual scores to extract 18 segments of the RCF. The algorithm performance was high, but not strictly equivalent to manual scoring.…”
Section: Introductionmentioning
confidence: 99%
“…However, these quantify the accuracy of the drawings by hand and in a subjective manner due to the complexity of the figures [23]. To address this, an automated scoring algorithm for the ROCF test was recently suggested and is based on cascaded deep neural networks, trained on scores from human expert raters [24].…”
Section: Introductionmentioning
confidence: 99%